Developing a Decision Support System for Assessing Bantara Rank Promotion Eligibility among Secondary School Scouts - Wawan Fadhilah; Riri Okra; Hari Antoni Musril; Sarwo Derta (Intellect : Indonesian Journal of Learning and Technological Innovation, 2026)
Assessing student eligibility for Bantara rank promotion requires an objective and systematic decision-making process. This study aimed to develop a technology-based decision support system to assist scout supervisors in evaluating students’ eligibility for Bantara rank promotion at a secondary school. The system was developed using the Scrum framework within an Agile development approach, including product backlog preparation, sprint planning, sprint implementation, sprint review, and retrospective activities. The development process was conducted over six weeks, comprising 26 effective working days. The system applied the Weighted Scoring Model to calculate and determine students’ promotion eligibility. The evaluation results showed a validity score of 0.97, a practicality score of 0.615, and an average effectiveness score of 0.93. These findings indicate that the developed system met the evaluation criteria used in the study and was considered feasible for supporting Bantara promotion assessments. The system provides a more structured basis for decision-making and may assist scout supervisors in conducting student assessments more consistently and objectively. Abstrak Penilaian kelayakan siswa untuk kenaikan pangkat Bantara memerlukan proses pengambilan keputusan yang objektif dan sistematis. Penelitian ini bertujuan untuk mengembangkan sistem pendukung keputusan berbasis teknologi guna membantu pembina pramuka dalam mengevaluasi kelayakan siswa untuk kenaikan pangkat Bantara di sebuah sekolah menengah. Sistem ini dikembangkan menggunakan kerangka kerja Scrum dalam pendekatan pengembangan Agile, yang mencakup persiapan product backlog, perencanaan sprint, pelaksanaan sprint, tinjauan sprint, dan kegiatan retrospektif. Proses pengembangan berlangsung selama enam minggu, yang terdiri dari 26 hari kerja efektif. Sistem ini menerapkan Model Penilaian Berbobot untuk menghitung dan menentukan kelayakan siswa dalam promosi. Hasil evaluasi menunjukkan skor validitas sebesar 0,97, skor kepraktisan sebesar 0,615, dan skor efektivitas rata-rata sebesar 0,93. Temuan ini menunjukkan bahwa sistem yang dikembangkan memenuhi kriteria evaluasi yang digunakan dalam penelitian ini dan dianggap layak untuk mendukung penilaian promosi Bantara. Sistem ini menyediakan landasan yang lebih terstruktur untuk pengambilan keputusan dan dapat membantu pembina pramuka dalam melakukan penilaian siswa secara lebih konsisten dan objektif.